Application of Instructional Design Models by Prospective Teacher Students - I Made Candiasa (Jurnal Pendidikan dan Pengajaran, 2022)
Prospective teacher students have been heavily involved in research on developing information and communication technology (ICT)-based teaching materials. The problems that exist until now often encounter obstacles in applying the right instructional system design model. This study is intended to formulate an instructional system design model that students can choose according to the characteristics of the ICT-based teaching materials developed. The study used an ex post facto approach with a descriptive method. A total of 528 student research reports in the 2017-2021 period became the population and the research sample. Observations were made on research reports to collect data, both quantitative and qualitative. Quantitative data were analyzed descriptively, while qualitative data were analyzed using the Miles, Huberman, and Saldana technique. The study found that there were six selected instructional system design models, of which the ADDIE model was the most chosen (37.50%), followed by ASSURE (20.45%), Dick & Carey (19.32%), Four-D (14.39%), Rapid Prototyping (6.82%), and the Kemp model being the least chosen model (1.52%). The main reason for choosing the model is the certainty of steps, ease of use, and user friendly, while many steps are not considered. As a result, the ADDIE, ASSURE, Dick & Carey, and Four-D models were widely chosen, while flexible models such as Kemp and Rapid Prototyping were not widely chosen because they require consideration in starting and ending development. Experience brings them the competence to choose the right instructional system design model.